2017
DOI: 10.1111/sms.12862
|View full text |Cite
|
Sign up to set email alerts
|

Muscle stiffness of posterior lower leg in runners with a history of medial tibial stress syndrome

Abstract: Previous history of medial tibial stress syndrome (MTSS) is a risk factor for MTSS relapse, which suggests that there might be some physical factors that are related to MTSS development in runners with a history of MTSS. The relationship between MTSS and muscle stiffness can be assessed in a cross-sectional study that measures muscle stiffness in subjects with a history of MTSS, who do not have pain at the time of measurement, and in those without a history of MTSS. The purpose of this study was to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
4
30
0
1
Order By: Relevance
“…Stiffness of the gastrocnemius reportedly has a strong correlation with plantar fasciitis [23]. Moreover, patients with a history of medial tibial stress syndrome had stiff FDLs [17] and increased stiffness of the FDL after running [16]. These results are similar to those of the our study, which show an increase in the stiffness of muscles related to running injuries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Stiffness of the gastrocnemius reportedly has a strong correlation with plantar fasciitis [23]. Moreover, patients with a history of medial tibial stress syndrome had stiff FDLs [17] and increased stiffness of the FDL after running [16]. These results are similar to those of the our study, which show an increase in the stiffness of muscles related to running injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Long distance running tends to decrease the height of the medial longitudinal arch, and to reduce arch exibility [14,15]. Moreover, the stiffness of the dynamic stabilizers of the arch, such as the tibialis posterior and the FDL, is increased after running [16,17]. However, the effects of the structure and exibility of the arch on changes in muscle stiffness after running are unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foot muscle weakness is also associated with a wide range of foot deformities and foot pain (e.g. [510]). Recent research has shown that foot muscle weakness may be associated with increased fall risk in the elderly due to the muscles’ role in stabilization and balance [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that running for 30 min increased the tibialis posterior and flexor digitorum longus stiffness [28]. Also, runners with an MTSS history demonstrated higher tibialis posterior and flexor digitorum longus stiffness than that in no MTSS history [29]. Therefore, rearfoot dominant pattern during drop jump may increase eccentric muscle contraction and traction force to the medial border of the tibia and related to MTSS.…”
Section: Discussionmentioning
confidence: 92%